PERANCANGAN DAN PEMBUATAN SISTEM PENDINGIN REM CAKRAM MENGGUNAKAN AIR SCOOP. PADA SEPEDA MOTOR MIO 125 - Hidayat, Rizal; Nuhgraha, Yoddy Agung (Jurnal Mahasiswa Terapan, 2026)
This research aims to design and manufacture a disc brake cooling system using an Air Scoop to improve motorcycle brake performance efficiency. The research background is based on the problem of overheating in disc brakes, which can cause brake fade and reduce braking effectiveness, especially under repeated or intensive braking conditions. The research method included designing the Air Scoop using aerodynamic principles, material selection, manufacturing processes, and static and dynamic testing with varying braking cycles. The results showed that using the Air Scoop reduced the average brake disc temperature by 10.6°C, or approximately 11.1%, compared to conditions without additional cooling. The maximum brake temperature with the Air Scoop was recorded at 93°C, while without the Air Scoop it reached 107°C. This temperature reduction demonstrates that the passive airflow-based cooling system can improve brake performance stability, reduce the risk of overheating, and minimize the potential for brake fade. With its simple and economical design, the Air Scoop has the potential to be implemented as a practical solution to improve motorcycle riding safety.